2014
DOI: 10.1016/j.epidem.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of changes in vaccine effectiveness and transmission contact rates on pertussis epidemiology

Abstract: The incidence of the highly infectious respiratory disease named pertussis or whooping cough has been increasing for the past two decades in different countries, as in much of the highly vaccinated world. A decrease in vaccine effectiveness over time, especially when acellular vaccines were used for primary doses and boosters, and pathogen adaptation to the immunity conferred by vaccines have been proposed as possible causes of the resurgence. The contributions of these factors are not expected to be the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
1
21
0
4
Order By: Relevance
“…Mathematical models have found that pertussis transmission is affected by both variations in VE and pertussis transmission rates. 30 Additional modeling may be helpful in further determining factors important for future interventions on a population basis.…”
Section: Figurementioning
confidence: 99%
“…Mathematical models have found that pertussis transmission is affected by both variations in VE and pertussis transmission rates. 30 Additional modeling may be helpful in further determining factors important for future interventions on a population basis.…”
Section: Figurementioning
confidence: 99%
“…Decreases in vaccine effectiveness over time, especially with acellular vaccines, have been proposed as a possible cause of the resurgence. This fact has been addressed by researchers and confirmed by various observational studies during the disease epidemics ( 2 , 26 - 28 ). Augmented T-helper-2 responses instead of T-helper-1 have also been suggested as an explanation for the waning antibody responses with these types of vaccines ( 29 ).…”
Section: Resultsmentioning
confidence: 69%
“…Genes encoding pertactin (Prn) and the tracheal colonization factor have been suggested to be responsible for changing the ability of colonization. Strains containing Prn2 and Prn3 have a higher potency for colonization versus those that have Prn1, and a higher colonization rate leads to increased transmissibility ( 2 ). Some researchers have also proposed that pathogen adaptation (increasing strain fitness) correlates with accelerated waning of immunity by decreasing the period in which pertussis vaccines are effective ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulamos variaciones temporales en distintos parámetros del modelo, como la eficacia y el contacto efectivo, que pueden asociarse a las posibles causas de la reemergencia, y correlacionamos los resultados obtenidos en estas simulaciones con datos epidemiológicos de distintos estados de EEUU. Estos estudios fueron publicados en la revista Epidemics [133]. Por otro lado hemos evaluado la incidencia de la enfermedad al contemplar los retrasos en la vacunación en las primeras tres dosis DTP utilizando datos de registros públicos.…”
Section: Vicente Zito Lemaunclassified